Minnets mönster och former: Minne och identitet i Linnea Axelssons epos Ædnan - Wasilewska-Chmura, Magdalena (Scandinavistica Vilnensis, 2023)
The article addresses the problem of memory and its role in shaping ethnic identity as shown in the epic poem Ædnan (2018) by Linnea Axelsson. I approach the poem from the postcolonial perspective focusing on Swedish policy towards the Sámi people, who were deprived of their land, culture, and identity. Various patterns of memory are embodied by the complex time structure of the poem. Its three parts follow three generations of the Sámi people. The first lost their cultural identity as a result of the colonisation of Northern Sweden and the hegemonic discourse against nomadic people. They became the Other for the dominant culture, and an object for disciplinary power. Next generation, which was supposed to assimilate with the Swedish society, felt rootless because their tradition had disappeared from collective memory. The third generation started struggling for their rights as an ethnic group constructing post-memory based on material traces and oral testimonies of the Sámi tradition. Last but not least, the choice of genre is significant, as it refers to the Western archive as a paradigm for memory culture. Thus, I regard the poem as an attempt to establish and explore an archive of the Sámi, which recognises the ethnic identity of the Sámi people on other grounds than the Western tradition does.
Keywords: Swedish literature; Linnea Axelsson; Ædnan; Sami culture; postcolonialism